(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The present study investigated the floristic structure and ecological role of Rourea afzelii stands in savannah, forest galleries and swampy areas to Cameroon. An 80 m x 50 m transect method was undertaken to measure floristic diversity using Shannon index, Pielou equitability, Simpson’s index and the importance value index. The structure of Rourea afzelii stands is determined by density, basal area and biovolume. The results of this study show that Rourea afzelii stands are more diversified in savannah with a Shannon diversity index (ISH =4 ± 0.03bit). The highest log stability of Rourea afzelii stands is observed in the savannah (EQ=0.75 ± 0.008). The Simpson index of the Rourea afzelii stands is larger in the forest gallery (D=0.088 ± 0.0022). Rourea afzelii Stands are denser in savannah (113 ± 2.54 individuals/ha). The basal area and biovolume of Rourea afzelii stands are very high in swamp area (St=15.75 ± 0.02 m2/ha, Biov=9.08 ± 0.12 m3/ha). The diametric structure has an asymmetrical “L” shaped appearance, indicating a strong regeneration of Rourea afzelii Stands in the three sites studied. Rourea afzelii Stands in forest galleries sequestered more carbon (26.41 ± 0.0015 ton C/ha) than those in savannahs and swampy areas. This value corresponds to sequestration of carbon dioxide of 96.92 ± 0.82 ton CO2/ha. Economically, this corresponds to the CDM carbon price (290.77± 3.332 Euros/ha), a Voluntary Market Carbon Price of 455.54 ± 1.908 Euros/ha, a REDD + carbon price of 9692 ± 8.152 Euros/ha. In conclusion, the results of this study can be used in the context of protection and conservation as well as the domestication of such a species.